Penggunaan Metode Global dalam Meningkatkan Kemampuan Membaca Permulaan Anak Tunarungu di Kelas II SLB Dorkas Kakas - Anna Zega (Peneliti.net, 2021)
This study aims to determine the early reading ability of deaf children in class II SLB Dorkas Kakas. The research method used in this study is an experimental method with a single subject or Single Subject Research (SSR). This research technique uses two data collection techniques, namely data collection techniques in the form of tests and observations. The data analysis technique used in Experimental research with Single Subject Research (SSR) is to use simple descriptive statistics in order to obtain an overview of the situation after being given treatment. Data was collected by means of articulation and observation skills tests. The results of research on improving the initial reading ability in subjects can be seen by comparing the results in the baseline-1 phase, intervention phase, and baseline-2 phase. In the baseline-1 phase, the subject experienced an increase, with a frequency score of 53.75 in the first session, 46.25 in the second session and 55 in the third session. Although in the baseline-1 phase there was an increase, the increase obtained did not show a significant change and still in an unstable condition. In the intervention session, there was an increase in initial reading ability continuously in each intervention session. A significant increase occurred in each intervention session. Based on the results of the study, it was concluded that the Global method could improve the early reading ability of deaf children in elementary grade II at SLB Dorkas Kakas.